Solve: -x^4 + 200 = 102x^2

-x^4-102x^2+200=0
(-x^2)^2-102(x^2)+200=0
(x^2-51)(x^2+51)(x-20)(x-10)

I'm stuck at this point

1 answer

Your last line makes absolutely no sense.
Just multiply the first terms in each bracket all together, you would get x^6 !!! and your last term would be -520200 !!!

Also I think you have a type.
If your equation is
+x^4 + 200 = 102x^2 it works out very nicely, so I am going to assume that the -x^4 is incorrect.

x^4 - 102x^2 + 200 = 0
(x^2 - 2)(x^2 - 100) = 0

so x = ±√2 or x = ±10